Respuesta :

Answer:

[tex]x=-\dfrac{17}{26}[/tex]

Step-by-step explanation:

[tex]4(7x-1)=3(2x+1)-4(x+6)[/tex]

Expand parentheses:

[tex]28x-4=6x+3-4x-24[/tex]

Combine like terms:

[tex]28x-4=2x-21[/tex]

Subtract 2x from both sides:

[tex]26x-4=-21[/tex]

Add 4 to both sides:

[tex]26x=-17[/tex]

Divide both sides by 26:

[tex]x=-\dfrac{17}{26}[/tex]

Hope this helps!

Hi1315

Answer:

[tex]x = \frac{ - 17}{26} \\ \\ [/tex]

Step-by-step explanation:

[tex]4(7x - 1) = 3(2x + 1) - 4(x + 6) \\ 28x - 4 = 6x + 3 - 4x - 24 \\ 28x - 6x + 4x = 4 + 3 - 24 \\ 26x = - 17\\ \frac{26x}{26} = \frac{ - 17}{26} \\ x = \frac{ - 17}{26} \\ [/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!